Real-world treatment patterns and clinical outcomes in patients with AML unfit for first-line intensive chemotherapy*. Issue 4 (21st March 2022) - Miyamoto, Toshihiro; Sanford, David; Tomuleasa, Ciprian; Hsiao, Hui-Hua; Olivera, Leonardo José Enciso; Enjeti, Anoop Kumar; Gimenez Conca, Alberto; Castillo, Teresa Bernal del; Girshova, Larisa; Martelli, Maria Paola; Guvenc, Birol; Delgado, Alexander; et al.
Abstract: Acute myeloid leukemia (AML) predominantly affects the elderly, and prognosis declines with age. Induction chemotherapy plus consolidation therapy is standard of care for fit patients; options for unfit patients include hypomethylating agents (HMA), low-dose cytarabine (LDAC), targeted therapies, and best supportive care (BSC). This retrospective chart review evaluated clinical outcomes in unfit patients with AML who initiated first-line treatment or BSC 01/01/2015–12/31/2018. Overall survival (OS), progression-free survival (PFS), time-to-treatment failure (TTF), and response rates were assessed. Of 1762 patients, 1310 received systemic therapies: 809 HMA, 199 LDAC, and 302 other therapies; 452 received BSC. Median OS was 9.9, 7.9, 5.4, and 2.5 months for HMA, LDAC, other, and BSC, respectively. Median PFS was 7.5, 5.3, 4.1, and 2.1 months for HMA, LDAC, other, and BSC, respectively; median TTF was 4.9, 2.1, 2.2, and 2.1 months, respectively. Our findings highlight the unmet need for novel therapies for unfit patients.